PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPAS PADA PESERTA DIDIK KELAS VSD INPRES SALUTTOWA KECAMATAN TINGGIMONCONG KABUPATEN GOWA - Nur Rahmadhani Syam; Nurlina; Nurfadilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nur Rahmadhani Syam, 2026. The Application of the Project-Based Learning Model on IPAS Learning Outcomes Among Fifth-Grade Students at SD Inpres Saluttowa, Tinggimoncong Subdistrict, Gowa Regency. Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Advisors: Nurlina and Nurfadillah. This study aims to describe the improvement in the IPAS learning outcomes of fifth-grade students through the implementation of the Project-Based Learning model. This study was motivated by the low learning outcomes of students in the IPAS subject. The study used a quantitative approach with a pre-experimental design and a one-group pretest-posttest design. The research subjects were all 24 fifth-grade students at SD Inpres Saluttowa. Data collection was conducted through learning achievement tests before the treatment (pretest) and after the treatment (posttest). The data were analyzed using descriptive statistical analysis and the N-Gain test. The results of the study indicate that there was an improvement in students’ IPAS learning outcomes following the implementation of the Project-Based Learning model. The students’ average score on the pretest, which was 60.75, increased to 89.33 on the posttest. All students achieved scores above the established Learning Objective Achievement Criteria (KKTP), which is 75. Based on these results, it can be concluded that the implementation of the Project-Based Learning model is effective in improving the IPAS learning outcomes of fifth-grade students at SD Inpres Saluttowa in Tinggimoncong Subdistrict, Gowa Regency.